Analisis Pengelolaan Aset Tetap Pada Badan Pendapatan Daerah (BAPENDA) Kabupaten Kolaka - Andi Iswan Muharram; Nichen .; Sriayu Pracita; Fahmi Sahlan (CV. ITTC INDONESIA, 2024)
Assets are an important element that must be managed well, because they support the success of operational activities in the regional government administration. The objective of this investigation is to find out whether asset management is implemented in accordance with the Regulation of the Minister of the Interior Number 7 of 2024 concerning amendments to the Regulation of the Minister of the Interior Number 19 of 2016, and to find out what obstacles are encountered when reporting on fixed assets. active in Kolaka Regency. The research method used is qualitative descriptive research. The data used in this research is secondary data. The research results show that the implementation of fixed asset management carried out by BAPENDA Kolaka Regency has been carried out thoroughly in accordance with Permendagri Number 19 of 2016 on the Technical Guidelines for Regional Property Management. , which has now been changed to Permendagri Number 7 Year 2024 concerning amendments to the Regulation of the Minister of the Interior Number 19 of 2016. Analysis of compliance with the implementation of legislation relating to the implementation of fixed asset management carried out by Kolaka Regency with the Minister of Internal Affairs Regulation Number 7 of 2024, so far there are still things that do not comply with legal regulations, such as the preparation of maintenance cards, which are related to the results of the maintenance that has been carried out. However, this does not hinder asset management.